Modern languages - Kohl, Katrin M. (Katrin Maria) 1956- (Cambridge, [England] Polity Press, 2021)
"A star scholar's passionate treatise on how learning other languages can change how we see the world, for the better"--Provided by publisher.
Includes bibliographical references (pages 130-145) and index.
Keywords: Languages, Modern -- Study and teaching; Language and languages -- Study and teaching; Language and culture